Adsorption of small molecules on helical gold nanorods: A relativistic density functional study. Issue 27 (11th August 2014) - Liu, Xiao‐Jing; Hamilton, Ian
<x xml:space="preserve">Abstract</x> We study the adsorption of a variety of small molecules on helical gold nanorods using relativistic density functional theory. We focus on Au40 which consists of a central linear strand of five gold atoms with seven helical strands of five gold atoms on a coaxial tube. All molecules preferentially adsorb at a single low‐coordinated gold atom on the coaxial tube at an end of Au40. In most cases, there is significant charge transfer (CT) between Au40 and the adsorbate, for CO and NO2, there is CT from the Au40 to adsorbate while for all other molecules there is CT from the adsorbate to Au40. Thus, Au40‐adsorbate can be described as a donor–accepter complex and we use charge decomposition analysis to better understand the adsorption process. We determine the adsorption energy order to be C5H5N >NO2 > CO > NH3 > CH2CH2 > CH2CHCHO > NO > HCCH > H2S > SO2 > HCN > CH3OH > H2CO > O2 > H2O > CH4 > N2. We find that the AuC, AuN, AuS, and AuO bonds are surprisingly strong, with clear implications for reactivity enhancement of the adsorbate. The AuH bond is relatively weak but, for interactions via an H atom that is bonded to a carbon atom (e.g., CH4), we find that there is large charge polarization of the AuHC moiety and partial activation of the inert CH bond. Although the AuS and AuO bonds are generally weaker than the AuC and AuN bonds, we find that adsorption of H2S or H2O causes greater distortion of Au40 in the binding region. However, the degree of distortion is small and the helical structure is retained, demonstrating the stability of the helical Au40 nanorod under perturbations. © 2014 Wiley Periodicals, Inc.